Adaptive observer‐based integral sliding mode control of a piezoelectric nano‐manipulator. Issue 14 (18th July 2019) - Zhang, Yangming; Yan, Peng
Abstract : In this study, the authors propose an adaptive observer‐based integral sliding mode control scheme to support ultra‐precision tracking of a multi‐axis piezoelectric nano‐manipulator. By introducing a modified Dahl model capable of approximating the hysteresis phenomenon, an adaptive observer is developed to compensate the impact of hysteresis, where an adaptive observer‐based integral sliding mode control architecture is further proposed with good robustness against model uncertainties. The gain of the sliding mode controller is adaptively estimated for the purposes of fast convergence, chattering alleviation and controller robustness. Finally, the proposed algorithm is implemented in real time on a PZT‐actuated nano‐manipulating stage, where good robustness and excellent tracking performance are successfully demonstrated, which outperform representative algorithms in the literature.